A Robust Strategy for Photoinitiated Macromolecular Thiol‐Ene Radical Coupling Reaction with High‐Efficiency Based on a RAFT‐Generated Thiol‐Terminated PDPA Reactant. Issue 2 (20th October 2022) - Yan, Lei; Liu, Yuyang; Wang, Zhiwen; Liu, Huan
Abstract: Thiol‐ene radical coupling reaction exhibits high chemical selectivity and rapid kinetics. In particular, the experiment of photoinitiated reaction has the advantages of facile operation and short reaction time. However, there are few reports on its application in macromolecular thiol‐ene coupling reaction in the presence of polymeric chains containing amine moieties. On the one hand, an amine agent itself may be involved in photoreaction; and on the other hand, amine moieties can create an alkaline environment, which may retard thiol‐ene radical reaction. In this paper, a well‐defined A(B‐L)2 type miktoarm star copolymer unit is investigated and synthesized, together with further A(B‐L)2 C type one, by employing macromolecular thiol‐ene radical coupling reactions. In two copolymers, A, B, and C are poly( ε ‐caprolactone) (PCL), poly(2‐(diisopropylamino) ethyl methacrylate) (PDPA), and poly(2‐methacryloyloxyethyl phosphorylcholine) (PMPC) arms, respectively, and L is terpyridine (tpy) ligand group and locates at the end of B arm. Especially, the synthesis of A(B‐L)2 type molecular architecture involved that a PDPA reactant (tpy‐PDPA‐SH) contains both a thiol end‐group and pendant tertiary amine moieties. Herein, such a macromolecular thiol‐ene radical coupling reaction is investigated and a robust synthesis strategy is reported. Abstract : Photoinitiated thiol‐ene coupling reaction between two PCL‐based dienes and tpy‐PDPA‐SH for synthesizing A(B‐L)2 type miktoarm star copolymer PCL(‐ b ‐PDPA‐tpy)2 ‐OH is investigated. A robust coupling condition is given. Afterward, an A(B‐L)2 C type miktoarm star copolymer is further obtained.